Não somos daqueles que dominam a fé dos outros: tolerância, irenismo e liberdade de consciência em Jacó Armínio - Couto, Vinicius Magno Borges Nunes (2022)
Jacobus Arminius (1559-1609) was a pastor of the Dutch Reformed Church (1587-1603) and professor at the University of Leiden (1603-1609). He is best known for the debate on predestination and human freedom, matters which he was involved in theological debates in the 16th and 17th century Netherlands and which heated Dutch Protestantism in the same period. The present research, however, investigates aspects that have not yet been explored about this Dutch thinker on topics related to religious tolerance, irenicism and freedom of conscience, and aims to contribute to the historiography of tolerance and studies on Arminius, transcending the theological approaches linked to the tripod anthropology, hamartology and soteriology. It is an analytical-exploratory research of Arminius' primary sources in a perspective of the history of mentalities in its dimension of cultural history in dialogue with the contextualist historical method and the history of theology. It was found that, within the context of religious quarrels, Arminius added his voice to pre-modern thinkers who defended freedom of conscience and public and religious concord. The research also contributes to a biographical revisionism of Arminius, revisiting and re-evaluating some narratives established by C. Bags about Arminius having changed his thinking, as well as proposing a development of Arminius' thought in four phases.(AU)